An Atheist’s Guide to the Divine: Throwing Out the Bathwater but Keeping the Baby - Mirman, M. Chet (Research in the social scientific study of religion, 2012)
it is suggested that the enduring universality and intuitively compelling quality of belief in God is reflective not of its veracity but of the fact that it is simply human nature to believe. the present paper argues that the preoccupation with external spiritual entities, along with the universal propensity to take these reified projections literally, has diverted us from the more constructive task of fostering personal, spiritual transformation via a focus on the religiogenic object representations that underlie these projections. An object relations approach is used to redefine spirituality in a way that shifts the focus from external referents to internal psychic realities. Briefly discussed is a model of ego development that frames transcendence as an ego experience rather than a metaphysical statement, faith as an attitude rather than a belief, and the experience of God as an entirely internal process. Also addressed are the implications of recent work pointing to the existence of two processing systems, one of which enables us to function in the material world, the other in the world of relationships, including a relationship with one’s religiogenic internal object representation (i.e., the God image).